A Systematic Review of the Sinonasal Microbiome in Chronic Rhinosinusitis. Issue 3 (May 2016) - Anderson, Martin; Stokken, Janalee; Sanford, Thomas; Aurora, Rajeev; Sindwani, Raj
Background: The interaction between the host and microorganisms in chronic rhinosinusitis (CRS) is poorly understood and is a growing area of interest. More recently, methodologies have been developed to assess the microbiome without the use of culture by analyzing the bacterial 16S ribosomal RNA gene. We reviewed the microbiome literature to better understand the role of microbes in CRS. Methods: Systematic review of studies that used the 16S ribosomal RNA gene deep sequencing. Results: Nine publications met the search criteria. Eight studies evaluated the microbiome in controls (total, 83 subjects; range, 3-28 per study), whereas six of the studies included patients with CRS (total, 121 patients; range, 7-43 per study). Various sequencing techniques, primers, sample sites, and extraction methods were used. Of the articles that specified the number of taxa in controls, an average of 1587 taxa were identified (range, 911-2330). Significant heterogeneity was noted among the studies; however, Firmicutes, Actinobacteria, and Bacteroides phyla were identified in every sample of control patients and patients with CRS. Three of the studies showed enrichment to some degree of Staphylococcus aureus in patients with CRS. The total bacterial burden in CRS was similar to the controls. One study demonstrated a decrease in diversity, whereas other studies did not show any changes in CRS when compared with controls. Conclusion: Although there are common phyla present in both control patients and patients with CRS, no consistent enrichment of any particular taxon was identified. Our findings indicated that there was no clear single causative microbe in CRS. More studies are needed to better understand the significance of the host interaction with the microbiome and the role it plays in CRS.